Effects of vascular compression on the rostral ventrolateral medulla for blood pressure variability in stroke patients. Issue 12 (December 2020) - Nezu, Tomohisa; Hosomi, Naohisa; Kuzume, Daisuke; Naito, Hiroyuki; Aoki, Shiro; Morimoto, Yuko; Kinboshi, Masato; Shiga, Yuji; Kinoshita, Naoto; Ueno, Hiroki; Maruyama, Hirofumi
Abstract : Backgrounds: Vascular compression of the rostral ventrolateral medulla (RVLM) has been associated with hypertension or blood pressure (BP) variability. For acute ischemic stroke patients, increased BP variability may cause poor functional outcomes. We tested the hypothesis that RVLM compression was associated with increased BP variability or stroke outcome in acute ischemic stroke patients. Methods: Acute ischemic stroke patients ( n  = 622) with 24-h ambulatory BP monitoring during the subacute phase of stroke (median 9 days from onset) were retrospectively studied. Variability in BP was evaluated with the SD and coefficient of variation of SBP and DBP. The morning surge was also evaluated. The presence of RVLM compression was evaluated using time-of-flight three-dimensional MRI. A poor outcome was defined as a modified Rankin Scale score of 3–6 at 3 months. Results: Patients with RVLM compression ( n  = 213) had significantly higher 24-h SBP mean, 24-h SBP SD, 24-h SBP coefficient of variation, 24-h DBP mean, 24-h DBP SD, and 24-h DBP coefficient of variation values and a higher prevalence of morning surge than those without ( n  = 409). Multiple regression analysis revealed that RVLM compression was associated with increased SBP variability, DBP variability, and morning surge. Despite the significant association between RVLM compression and BP variability, RVLM compression was not associated with poor stroke outcome. Conclusion: Although RVLM compression was closely associated with BP variability in the subacute ischemic stroke phase, an effect of RVLM compression on stroke outcome was not observed. Abstract : Supplemental Digital Content is available in the text